Cultural Competency of Ni-Vanuatu Librarians: Vanuatu Libraries Contribution to the Nation's Vibrant Cultural Identity. Issue 4 (2nd October 2021) - Alenzuela, Reysa
ABSTRACT: Libraries play an important role in promoting cultural and language diversity, preserving knowledge and supporting educational goals. This paper discusses the ni-Vanuatu Librarians cultural competencies and examines the current programs and prospective initiatives that can contribute to a vibrant cultural identity of the nation. To have a baseline data, the inquiry started with a survey based on the American Library Association Diversity Standards: Cultural Competency for Academic Libraries . This standard was found appropriate as similar concepts are useful in Vanuatu, although some modification for context was required. Overall, the respondents are aware of their competence but recognise that cultural competence has not been integrated into work. Limitations, such as lack of funding, lack of resources making cultural competence not priority were reasons why they have not developed or applied these concepts. The results of this study provides insights on the applicability of this standard for libraries in the Pacific to develop the cultural competence of their staff.